2021
DOI: 10.3389/fpsyg.2021.647502
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patient Experience of Uncertainty While Waiting for Genome Sequencing Results

Abstract: There is limited knowledge about cancer patients' experiences of uncertainty while waiting for genome sequencing results, and whether prolonged uncertainty contributes to psychological factors in this context. To investigate uncertainty in patients with a cancer of likely hereditary origin while waiting for genome sequencing results, we collected questionnaire and interview data at baseline, and at three and 12 months follow up (prior to receiving results). Participants (N = 353) had negative attitudes towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…1 Patients with cancer are known to be at risk for psychological distress and lower quality of life. 20 Research has demonstrated the independent role of uncertainty on psychological well-being, 11,21 which can compound these psychological risks and pose a threat to patients' employment of effective coping skills, adaptation to a cancer diagnosis, and health-related quality of life. 22,23 Additionally, heightened perceptions of uncertainty among patients with cancer have been shown to be associated with negative impacts on health behavior, 24 and therefore represent a critical consideration in terms of patient-centered care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Patients with cancer are known to be at risk for psychological distress and lower quality of life. 20 Research has demonstrated the independent role of uncertainty on psychological well-being, 11,21 which can compound these psychological risks and pose a threat to patients' employment of effective coping skills, adaptation to a cancer diagnosis, and health-related quality of life. 22,23 Additionally, heightened perceptions of uncertainty among patients with cancer have been shown to be associated with negative impacts on health behavior, 24 and therefore represent a critical consideration in terms of patient-centered care.…”
Section: Discussionmentioning
confidence: 99%
“…10 Individuals with rare or treatment-resistant cancer live with profound uncertainties, which often leaves them feeling more distressed than individuals with common cancers with more certain prognosis and management. 11,12 Patients with cancer are often interested in learning genomic results related to their tumor, which introduces additional uncertainties inherent in sequencing that exceed those of other types of medical information 1 and must be managed on top of the uncertainties of the cancer trajectory. Motivation may be aimed at reducing uncertainty regarding the etiology of their cancer and the potential for targeted cancer treatment, which in the context of rare or treatment-resistant cancer likely leads to disappointment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations